Analysis of Coal Ash for Trace Elements and their Geo-environmental Implications - Harwant, Singh; Prabir, Kumar Kolay (Springer International Publishing, 2007)
This study determined the content of trace elements in coal ash collected from a coal-fired thermal power plant using local coal from Sawarak, Malaysia. This is crucial for the potential impact on the geoenvironment from its disposal and utilization; as coal ash has recently been produced locally in substantial amounts and very limited data is available. The trace elements concentrations presents in coal ashes are compared with the reported coal ash concentrations and the risk for the local wet tropical geoenvironment from the perspective of its vulnerability to these is studied for an indication of potential environmental implications on the wet tropics. The trace elements were found to be in concentrations that, if applied or inadvertently released into the environmental media, present a potential hazard and further necessary research in this regard is indicated.